2021
DOI: 10.3390/cimb43020073
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Diabetes in Patients Affected by Liang-Wang Syndrome Carrying KCNMA1 Variant p.(Gly375Arg) Suggest a Potential Role of Ca2+ and Voltage-Activated K+ Channel Activity in Human Insulin Secretion

Abstract: Liang-Wang syndrome (LIWAS) is a polymalformative syndrome first described in 2019 caused by heterozygous mutation of the KCNMA1 gene encoding the Ca2+ and voltage-activated K+ channel (BKC). The KCNMA1 variant p.(Gly356Arg) abolishes the function of BKC and blocks the generation of K+ current. The phenotype of this variant includes developmental delay, and visceral and connective tissue malformations. So far, only three cases of LWAS have been described, one of which also had neonatal diabetes (ND). We presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…13 However, the clinical features had a larger variability with regard to ataxia, tremor, epilepsy, dysmorphism and developmental and other features. 13 Moreover, our study 13 and another recent study by Mameli et al 14 suggest that type I diabetes may be another clinical feature of Liang-Wang syndrome. Interestingly, homozygous KCNMA1 variants were also reported, for example, p.(Y676Lfs*7) detected in two siblings with epilepsy, developmental delay and severe cerebellar atrophy, and p.(R458Ter) identified in a patient with paroxysmal dyskinesia, epilepsy, intellectual delay and corticospinal-cerebellar tract atrophy.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…13 However, the clinical features had a larger variability with regard to ataxia, tremor, epilepsy, dysmorphism and developmental and other features. 13 Moreover, our study 13 and another recent study by Mameli et al 14 suggest that type I diabetes may be another clinical feature of Liang-Wang syndrome. Interestingly, homozygous KCNMA1 variants were also reported, for example, p.(Y676Lfs*7) detected in two siblings with epilepsy, developmental delay and severe cerebellar atrophy, and p.(R458Ter) identified in a patient with paroxysmal dyskinesia, epilepsy, intellectual delay and corticospinal-cerebellar tract atrophy.…”
Section: Introductionsupporting
confidence: 65%
“…Interestingly, homozygous KCNMA1 variants were also reported, for example, p.(Y676Lfs*7) detected in two siblings with epilepsy, developmental delay and severe cerebellar atrophy, and p.(R458Ter) identified in a patient with paroxysmal dyskinesia, epilepsy, intellectual delay and corticospinal‐cerebellar tract atrophy 15,16 . To date, 19 pathogenic KCNMA1 variants have been reported to be associated with different neurological disorders in 42 patients 14,17‐20 . Three of them acted by GOF, nine by LOF and three without functional characterization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this broad spectrum of developmental and neurological features, previous work from the Authors of the present study also demonstrated that heterozygous LoF KCNMA1 variants (the G375R, in particular) can also cause severe visceral and cardiovascular malformations, bone dysplasia, and facial dysmorphic features, 10 a phenotype identified as the Liang‐Wang syndrome (OMIM #618729). Notably, the same variant has also been recently described in a newborn presenting with neonatal diabetes with persistent insulin‐dependent hyperglycemia, in addition to congenital facial and internal organs abnormalities, a result suggestive of a critical role for K Ca channels in controlling insulin release from pancreatic β‐cells 11 …”
Section: Figurementioning
confidence: 74%
“…Notably, the same variant has also been recently described in a newborn presenting with neonatal diabetes with persistent insulin-dependent hyperglycemia, in addition to congenital facial and internal organs abnormalities, a result suggestive of a critical role for K Ca channels in controlling insulin release from pancreatic βcells. 11 In addition to those heterozygous variants, two additional homozygous KCNMA1 variants (R458X, Y676fs), 12,13 predicted to result in truncated, less functional protein, have been each identified in two patients affected with seizures, severe developmental delay, and non-progressive cerebellar atrophy; as a result, a third phenotype is now described in OMIM as associated with KCNMA1 variants, described as cerebellar atrophy, developmental delay, and seizures (CADEDS; #617643).…”
mentioning
confidence: 99%